“ALL ROADS LEAD TO ‘PERVERBS’’: HARRY MATHEWS’S SELECTED DECLARATIONS OF DEPEND-ENCE (1977) - Mieder, Wolfgang (Proverbium - Yearbook, 2019)
The manipulative change of traditional proverbs into innovative anti-proverbs is nothing new. In fact, the playful rearrangement of proverb halves into insightful or nonsensical creations has been practiced by such aphoristic writers and poets as Friedrich Nietzsche, Ber-tolt Brecht, Paul Éluard, Franz Fühmann, Marcel Bénabou, Paul Mul-doon, and others. The art of scrambling proverbs was practiced in particular by several members of the French avant-garde group of writers and intellectuals called Oulipo (Ouvroir de Littérature Potentielle). The American author Harry Mathews (1930-2017) was one of its prolific members who excelled with his enumerative poems based on various patterns of proverb fragments. While he published such tour-de-force poetic texts in French, he also wrote a most unique book in English with the title Selected Declarations of Dependence (1977). The first part is a love story of sorts based on the 185 words that appear in 46 common English proverbs. Proverb halves are interspersed in this prose, but there are also multiple poetic texts that employ parts of prov-erbs in certain patters and as anaphora and leitmotifs. The second half is made up of 106 paraphrases of what he calls “perverbes”, i.e., anti-proverbs made up of two proverb halves. It is up to the readers to find which perverb (the English spelling) belongs to which paraphrase. All of this is meant to entertain and challenge readers into becoming active participants in these texts that at times make sense but also remain without any meaning. The entire book is conceived as an intellectual game with its own riddles and perplexities but also its playful humor that should intrigue and delight paremiologists everywhere.